DEBTOR’S RIGHTS AND OBLIGATIONS DURING COURT ORDER ENFORCEMENT, CAUSES OF PROBLEMS THAT MAY ARISE AND THE METHODS OF OVERCOMING THESE PROBLEMS - Elisabedashvili, Davit (European Scientific Journal, ESJ, 2015)
Everything has his pros and cons. Debtor’s rights and obligations during court order enforcement, causes of problems that may arise. This problem is in the whole country, not just in one city or in one social class. A very large number of families from everywhere around Georgia have been affected. How and where it started will be discussed below in the text. Rights of creditors and debtors overlap in many aspects. We need to be very careful when sorting out this issue. We cannot under any circumstances make a decision with a benefit of one party while the other party will suffer losses. Georgian law on “Law Enforcement” does not support in any ways rights of debtors and all the procedures highlighted are towards forcing the debtor to pay off the debt. At this stage based on the current law, current socio-economic problems, statistics, ways on sorting out the problem, this object of studies is very important and has a very high intrinsic value in its theoretical part as well as in its practical part. If the right approach is taken it is possible to minimise the need to protect rights of creditors or debtors in the futures, because every party will be fully aware of their abilities and punishments for failures to fulfil their obligations, before signing the contract